Readiness and Effectiveness of Synchronous Online Teaching and Learning in Higher Education during COVID-19 Pandemic - Low Han Lun; Adam Daniel Effendi; Dzeti Farhah Mohshim; Nabilla Afzan Abdul Aziz; Noreen Izza Arshad; Mitra Mohd Addi (Journal of Advanced Research in Computing and Applications, 2024)
The abrupt or rapid shift to online learning has pushed students and lecturers to accept the online learning and teaching mode. Therefore, there is a necessity to study students’ and educators’ readiness in adopting online teaching and learning. Relating to this, the main objective of this paper is to assess students’ and lecturers’ fitness levels in adapting to online teaching and learning at a selected University. This study focuses on evaluating the online readiness levels that relates to teaching and learning preferences, technology, usefulness and ease of use of the employed e-learning system. The participants of the study involved undergraduate students and lecturers of an engineering department at a selected University. The survey questionnaire survey was distributed to 120 students and 17 lecturers. The responses had reflected moderate fitness level of preference towards online teaching and learning and having adequate digital devices and facilities including Internet to conduct learning virtually. However, significant improvement is encouraged towards expanding the current e-learning platform. The absence of active interaction features and non-verbal cues between teachers and students have been the most reported issue of the current e-learning platform. Some other issues raised by students include the excessive workloads on projects converted online, communication difficulty, and the lack of motivation to study remotely away from the common learning group. The outcome of this study is valuable as to review the current online teaching and learning implementation and its acceptance among students and educators in the University for future improvement and strategic decision making.